A clinical and etiological spectrum of thrombocytopenia in adult patients - Dr. Mital Gamit; Dr. Gunvanti Rathod (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Thrombocytopenia is not a disease but is a diagnosis. The detailed knowledge must be acquired from patients who have thrombocytopenia. This study aimed to determine the relative frequency of different disease conditions presenting as newly found thrombocytopenia in adult patients and to determine whether a low platelet count or presence of bleeding manifestation was considered more often as an indicator for platelet transfusion.Materials and Methods: This retrospective study was done at a tertiary care hospital during the period of November 2018 to October 2019. Blood samples were analyzed for Complete Blood Count (CBC). The clinicopathological correlation was done and the findings were tabulated.Results: In present study, the sex distribution of patients of thrombocytopenia was noted as 55.75% male and 44.25% female. The present study showed that most of the cases of thrombocytopenia belonged to the age group of 18-29 years (45%), followed by the age group of 30-39 years (28.75%), the least being in the age group of over 80 years (2.0%). Most of the patients presented with Grade 1 thrombocytopenia (49.5%). The most common etiology responsible for newly diagnosed thrombocytopenia in adult patients was found to be dengue/dengue-like fever (41.75%).Conclusion: It can be concluded from this study that the most common causes for thrombocytopenia are infective causes e.g. dengue, malaria.